Pengelompokkan Kecamatan Berdasarkan Alat Kontrasepsi Menggunakan Algoritma K-Means - Putri Puspita Sari; Kismiantini Kismiantini (Seminar Nasional Official Statistics, 2022)
Family Planning (KB) participants are couples of childbearing age who are using one of the modern contraceptives in the year of implementation of family data collection. The purpose of this study was to classify sub-districts in the DI Yogyakarta Province based on family planning contraceptives using the K-Means algorithm. The data used is the percentage of contraceptive users in the DI Yogyakarta Province in 2021 obtained from the Population and Family Information System. The research variables were 7 contraceptives, namely IUD, MOW, MOP, condoms, implants, injections, and pills. Determining the number of clusters using Principal Component Analysis obtained 2 clusters with within cluster sum of squares of 45.6%. The results showed that cluster 1 (30 sub-districts) consisted of IUD, MOW, MOP, and condoms. Cluster 2 (48 sub-districts) consists of implants, injections, and pills. Clusters are named based on the place where the contraceptive device was installed, cluster 1 for sex, and cluster 2 for non-gender.